WOMAN STEREOTYPE IN “IN STYLE” MAGAZINE CONSTRUCTED THROUGH LEXICAL CHOICE AND SYNTACTICAL STRUCTURE - DIANA, ADDIENA RYZKA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: women stereotype, beauty advertisement, lexical choice and syntacticalstructureThis study aimed at finding out how women are stereotyped by beauty advertisement by “In Style” magazine. This study is mainly focuses on Semantic which the means are to uncover the stereotype. The analysis was based on Lexical Choice and Syntactical Structure theory. It demonstrates how the ideology of ‘beauty’ is produced and reproduced through advertisement in Indonesia women’s magazines.The writer investigated the lexical choices and syntactical structure used to constructwomen. Qualitative approach using content or document analysis was applied in thisstudy. The data of this research were twenty nine utterances of beauty productadvertisement occurring in “In Style” magazine from October – November 2014edition.This study reveals that there are three meanings constructed emerged. Those meanings suggest that women are stereotyped as follows: (1) beautiful woman shouldapply make-up on, (2) women should look fresh and stay young and (3) women couldbecome beautiful in fast and easy way. Moreover, the magazine promotes an idealized lifestyle and manipulates readers through advertisement. This study alsorevealed how the ideology of beauty is constructed and reconstructed throughmagazines by stereotyping how beauty products are synonymous with a better life.  The writer suggests that the next writer also cover up deeper research by usingcase study because it is important to use participants point of view as a part of thesociety semantic related with language as a form of social practice.